The Influence of Education Service Quality on School Selection Interest with School Image as a Mediating Variable at SMA X Bandung - Susanti Setiawaty; Bobby Wiryawan Saputra (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of educational service quality on school choice interest with school image as a mediating variable at SMA X in Bandung City. The quality of education services is measured based on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. School image is assessed through personality, reputation, value, and corporate identity. School choice interest includes attention, interest, need, enjoyment, and motivation. A quantitative approach was applied using a survey method involving 238 respondents consisting of students and parents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that: (1) educational service quality has a positive and significant effect on school image; (2) educational service quality has a positive and significant effect on school choice interest; (3) school image has a positive and significant effect on school choice interest; and (4) school image significantly mediates the relationship between educational service quality and school choice interest. The findings highlight the importance of enhancing educational service quality to build a strong school image and attract student and parent interest in choosing a school.